2019
DOI: 10.21776/ub.jam.2019.017.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotypes in Indonesian Public Companies’ Performance

Abstract: Gender equality is one important item from the United Nation's Sustainable Development Goals (SDGs). It makes a gender gap in companies' top management becomes valuable to be studied because people still have a stereotype that leadership is a masculine job.This research will test the effect of performance, payment, bankruptcy risk, and earnings management. Data is taken from Indonesian public companies in 2016 using means different statistical test. The result shows that 30.9% or minority corporation have a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Only a few companies have a female director since a gender stereotype stating that men are better at leadership than women. In contrast, the research found that women can lead better than men (Rahayu et al, 2019).…”
Section: Introductionmentioning
confidence: 81%
“…Only a few companies have a female director since a gender stereotype stating that men are better at leadership than women. In contrast, the research found that women can lead better than men (Rahayu et al, 2019).…”
Section: Introductionmentioning
confidence: 81%
“…The performance of governance in state-owned companies that is not optimal means that management feels that it is not being monitored optimally by the company's board so that managers feel they have the opportunity to practice earnings management. On the other hand, there is a tendency to compensate top managers based on company performance (Rahayu et al, 2019) will strengthen the desire of managers to practice earnings management with the method of increasing profits because the greater the profit earned, the greater the compensation received by the manager.…”
Section: Corporate Governance and Earnings Mangementmentioning
confidence: 99%
“…Outsourcing is the delegation or transfer of some company processes to a service provider company based on the administration agreed upon by both companies (Suyanto & Nugroho, 2017). Wahyuni et al (2013) explained that in the last decade, Indonesia's outsourcing process has evolved from traditional to strategic. It was traditionally associated with units of non-production activities such as health services, catering, security, hygiene, and the like but is now more able to expand towards more essential activities.…”
Section: Introductionmentioning
confidence: 99%